THE BACCALAUREATE, THE FIRST LABORATORY OF IMPERIAL RESURRECTION: THE SCHOOL TEXTBOOKS OF FRANCO’S REGIME AND MEXICAN INDEPENDENCE,(1940-1950) (Tzintzun, Revista de Estudios Históricos, 2024)
n the core of power of the Francoist dictatorship, they were aware that in order tocompletely wipe out the legacy of the Second Republic, weapons alone were notenough. It was in this context that the regime’s ideologues considered that the onlyway to erase the republican culture from memory, and to begin the ideological processof restoring the empire and Hispanic culture, was to transfer the war to a new field:education. On this battlefield, the history textbooks of Franco’s baccalaureate becamethe ideal instruments for rooting in the imagination of Spanish students the projectof nation and national identity that the Franco regime sought to perpetuate. Inparticular, to achieve the creation of a “New Man” in charge of building the “NewSpain”. For this paper we carried out a historical and historiographical analysis ofhow Franco’s school textbooks interpreted and justified the loss of the AmericanEmpire, paying special attention to the Mexican insurgent process.
Keywords: Francoist Baccalaureate; Textbooks; National Identity; Nation-State; Empire and Emancipation